"Claw hand with a unilateral onset" as a regional variant of Guillain-Barre' syndrome: A case report. Issue 20 (15th May 2020) - Wang, Suhong; Zhao, Shuxin; Zhang, Zhecheng
Abstract: Rationale: Although distal nerves located at sites prone to compression are susceptible to autoimmune attack, Guillain-Barre' syndrome (GBS) with exclusive hand muscle involvement is rarely found in clinics. All reported patients presented with a special variant - finger extensor weakness, especially claw hand caused by predominant ulnar extensor involvement. Similar to typical GBS, these patients showed bilateral symmetric onset with rapid clinical progression. Patient concerns: A 62-year-old man with GBS was admitted to our hospital with unilateral onset of claw hand. He showed relatively slow progression and did not develop bilateral symmetric claw hands until 6 weeks later. Diagnoses: Eventually the patient was diagnosed as having a regional variant of GBS by neuronal electrophysiology and cerebrospinal fluid examinations. Interventions: This patient was treated with intravenous thrombolysis within 4.5 hours of onset. Eventually he was diagnosed as having a regional variant of GBS and was treated with gamma-globulin (400 mg/kg/d) for 5 consecutive days via intravenous infusion. Outcomes: The patient had a slow recovery with persistent mild finger extensor weakness. Lessons: This patient presented with unilateral onset of claw hand, and the diagnosis of acute ischemic stroke could not be excluded because of a short time window; hence, he was treated with intravenous thrombolysis within 4.5 hours of onset. Eventually he was diagnosed as having a regional variant of GBS. It is important that GBS should also be considered in patients with unilateral hand weakness and unknown aetiology in the early stages of disease.